THE EFFECT OF SAFFRON (ITS ACTIVE CONSTITUENT, CROCIN) ON THE CARDIOVASCULAR COMPLICATION AND DYSLIPIDEMIA IN STREPTOZOTOCIN INDUCED DIABETIC RATS - Altinoz, Eyup; Taskin, Emre; Oner, Zulal; Elbe, Hulya; Arslan, Belkis Atasever (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Diabetes mellitus (DM) causes serious complications such as coronary heart disease, atherosclerosis, nephropathy, retinopathyand neuropathy.Materials and Methods: Rats were randomly divided into three groups each containing 10 rats; control group, DM group; DM+crocin group.Normal saline was administered in the control and DM groups, and crocin was administered in DM+crocin group at a dose of 20 mg/kg bw/dayfor 21 days. Trunk blood and the hearth tissue were collected for histopathological and biochemical examination.Results: DM led to increment of MDA levels (p<0.05) and the serum levels of total cholesterol, TG, LDL and VLDL (p<0.05) and decrease ofGSH levels (p<0.01) compared to control group in serum and heart tissue. Diabetic rats were treated with crocin, MDA levels (p<0.05) and thelevels of total cholesterol, TG and VLDL decreased significantly, but GSH levels (p<0.05) increased remarkably compared to DM rats.Statistically significant increase in histopathological damage score was found in the DM group (p<0.0001). Histopathological changes markedlyregressed in DM+crocin group.Conclusion: Our results showed that crocin might prevent diabetes induced cardiovascular complications by reduction of oxidative stress anddyslipidemia.